Preparation of sodium alginate supramolecular gel beads and application of sodium alginate supramolecular gel beads in detection and adsorption of terbium and europium ions

The DPA/GB composite material prepared by doping and cross-linking DPA and sodium alginate solves the problem of detection and removal of rare earth elements in the water environment, achieves high-sensitivity detection and efficient adsorption, is low-cost, and is sustainable. sex.

CN119346073APending Publication Date: 2025-01-24GUIZHOU NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411562821.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively detect and remove rare earth elements, especially in water environments. The traditional adsorbent preparation cost is high, the environmental pollution is serious, and the dual-function visual sensing and adsorption performance are lacking.

Method used

A multifunctional composite material DPA/GB was prepared by doping 2,6-pyridinedicarboxylic acid (DPA) with sodium alginate (SA) and through a calcium ion cross-linking reaction, utilizing its supramolecular gel bead structure in aqueous solution. Realize visual detection and efficient adsorption of Tb3+/Eu3+.

Benefits of technology

A high sensitivity visual detection and efficient adsorption of TB3+/EU3+are realized. The detection limit is as low as 0.23/0.85 nm, the adsorption capacity is 270/301 mg/g, and the material cost is low, which is sustainable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

Visual detection and efficient adsorption / recovery of the rare earth ions have important practical significance on environmental and eco-friendly economic development. At present, development of sustainable materials integrating visual detection and efficient adsorption / recovery functions still has challenge. The invention provides a preparation method of sodium alginate supramolecular gel beads, which comprises the following steps: doping pyridine-2, 6-dicarboxylic acid (DPA) and sodium alginate (SA) by using calcium ions as a cross-linking agent to prepare hydrogel beads (DPA / GB) with high-density carboxyl groups and pyridine nitrogen atoms. The material shows relatively high sensitivity and excellent in-situ detection capability on terbium (Tb < 3 + >) and europium (Eu < 3 + >), and also has good anti-interference performance. In a wide concentration range of 0.2 to 1000 [mu] M and 6 to 600 [mu] M, the limit of detection (LOD) of DPA / GB to Tb < 3 + > and Eu < 3 + > is 0.23 nM and 0.85 nM, respectively. When the pH value is 5.02, the adsorption capacities of DPA / GB to Tb < 3 + > and Eu < 3 + > are respectively 270 mg / g and 301 mg / g (equivalent to 1.72 mmol / g and 1.98 mmol / g). The invention provides an experimental basis for visual detection and efficient removal of Tb < 3 + > / Eu < 3 + > in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material preparation and rare earth ion visual adsorption, and relates to the preparation of sodium alginate supramolecular gel beads and the application of the beads in the detection and adsorption of terbium and europium ions. Background Art

[0002] Rare earth elements are important strategic resources with unique luminescent, electrical and magnetic properties. They are widely used in high-tech applications such as permanent magnets in emerging fields such as optoelectronic devices, lasers, smart phones, and electric vehicles. However, their extensive use has led to an annual increase in global demand of about 5%. But in contrast, only about 1% of rare earth elements from electronic waste can be reused. In addition, as emerging pollutants, rare earth elements have posed potential health risks to humans and the environment. Therefore, in order to avoid these threats to the ecological environment, improve the recycling efficiency of rare earth elements, and develop a comprehensive research strategy for efficient detection and removal of rare earth elements, this approach has practical significance for water environment protection and human disease prevention.

[0003] To date, many methods have been developed for single specific functions, such as luminescent visual sensing, solvent extraction, liquid membrane separation, and adsorption. 3+ ) has the characteristics of linear luminescence, large Stocks shift, long fluorescence lifetime, and high color purity. Therefore, it has the advantages of simple operation, low cost, and high sensitivity. Traditional adsorbents, including metal oxides, activated carbon, and composite materials, have been used to adsorb REE 3+ . However, their preparation cost is relatively expensive and they are prone to environmental pollution. Their adsorption capacity is low due to the limited adsorption sites available on the materials themselves. In addition, traditional optical sensors / adsorbents lack detection / adsorption sites, which makes it a daunting challenge for them to simultaneously achieve the dual functions of visual sensing and adsorption performance. Therefore, integrating detection sites and adsorption sites into the same sustainable matrix may be the most effective strategy to achieve dual functions. But unfortunately, REE 3+ The optical properties of REEs are closely related to the coordinated H2O, and their characteristic luminescence is easily quenched by the vibration of the high-energy OH bond. 3+ ions have similar physical and chemical properties, and metal ions (Na + , K + Mg 2+ , Ba 2+ , Ca 2+ , Fe 3 + 、Al 3+ ) interference, the actual sample REE 3+The visual detection and removal of the PDMS have obvious interference. Therefore, the development of dual-functional sustainable materials faces great challenges. To the best of our knowledge, no corresponding reports have been found.

[0004] 2,6-Pyridinedicarboxylic acid (DPA) and REE 3+ The coordination interaction is strong, and the excited state (T1) energy is 25510 cm -1 , and Tb 3+ / Eu 3+ Excited state ( 5 D4 / 5 D0 is 20500 / 17500 cm -1 ) is smaller. It complies with the energy transfer rules proposed by Reinhoudt's and Latva's rules, making DPA sensitized Tb 3+ / Eu 3+ , and produces green / red characteristic emission. In addition, sodium alginate (SA) is a biopolymer with a large number of hydroxyl and carboxyl groups, which reacts with Ca in water to form 2+ , Ba 2+ and Mg 2+ Ionic crosslinking can produce hydrogel-based materials. SA contains abundant O-containing (hard base) structures, which can be used as REEs through electrostatic and coordination interactions. 3+ (Hard acid) provides active binding sites. Therefore, this patent uses DPA as Tb 3+ / Eu 3+ The sensitizer was grafted onto SA via intermolecular hydrogen bonds to prepare the multifunctional composite material DPA / GB. 3+ The visualization of the detection provides binding sites and also enhances the 3+ / Eu 3+ The multidentate chelating sites and porous structure of the composites are expected to promote the adsorption of REE 3+ coordination and encapsulation, thereby protecting them from the effects of quenchers.

[0005] The present invention prepares a sustainable hydrogel bead based on sodium alginate (DPA / GB), which can be used for Tb in aqueous solution due to its large number of exposed O- and N-containing sites and porous structure. 3+ / Eu 3+ Visual detection and adsorption. Summary of the invention

[0006] The invention aims to provide a method for preparing sodium alginate supramolecular gel beads and application thereof in the detection and adsorption of terbium and europium ions.

[0007] 1. Preparation and water content test of DPA / GB gel beads The preparation method of DPA / GB gel beads is as follows: sodium alginate (SA) is dissolved in deionized water to obtain a sodium alginate solution, pyridine-2,6-dicarboxylic acid (DPA) solution is slowly added under stirring conditions of 55-65°C, and stirring is continued for 10-15 hours to make it completely mixed; the obtained DPA sol is added dropwise into a 1 wt% calcium chloride solution, and after cross-linking reaction with calcium ions at room temperature for 1-3 hours, DPA / GB gel beads of uniform size are obtained.

[0008] The mass ratio of sodium alginate to pyridine-2,6-dicarboxylic acid is 75:2~40:1.

[0009] The water content in DPA / GB was estimated according to (Equation 1). Figure 1 As shown in the figure, DPA / GB is in the form of transparent spheres with an average diameter of about 4 mm and a weight of 48 mg. After freeze drying, the size of the compressed spheres was observed to decrease and the weight was reduced to 2.9 mg. This indicates that the water content of DPA / GB gel beads is 94%.

[0010] The TGA curve shows that ( Figure 1 d) DPA / GB has good thermal stability below 200°C, and the weight loss caused by free water or hydrogen-bonded water is about 94.13%. The moisture content (94.13%) is consistent with the result of freeze-drying treatment (94.03%).

[0011] 2. Structural Characterization of DPA / GB Gel Beads 1. FTIR and Raman spectroscopy analysis The chemical compositions of SA, DPA and DPA / GB were characterized and analyzed by Fourier transform infrared spectroscopy. Figure 2 As shown in a, in the infrared spectrum of SA, 3359, 1600, 1410, and 1020 cm -1 The characteristic absorption peaks at 2626 and 2540 cm -1 The absorption band at 1700 cm -1 and 1570 / 1410 cm -1 The infrared absorption at 2990-3660cm-1 was attributed to the C=O and C=N / pyridine rings of DPA. In the infrared spectrum of DPA / GB, the characteristic stretching vibration peak of SA showed a slight red shift; no new absorption peak appeared in the infrared spectrum of DPA / GB gel beads, but the characteristic peak of -OH connected to the carboxyl group of DPA disappeared. At the same time, -1The above infrared spectrum analysis shows that there is no covalent bond between DPA and SA. These changes are caused by the C=O···OH and C=N···OH hydrogen bonds formed between DPA and SA. In addition, a broad absorption peak appears in the Raman spectrum of DPA / GB ( Figure 2 b), which further proves the formation of hydrogen bonds; the C=O and C=N absorption peaks of DPA overlap in the infrared spectrum of DPA / GB, which may overlap with the bending vibration peaks of the carboxyl group in SA. This phenomenon is caused by the formation of hydrogen bonds or the interaction between the carboxyl group and Ca 2+ Coordination between ions.

[0012] 2. XPS, SEM, XRD and BET characterization analysis The full XPS spectrum of DPA / GB is as follows Figure 3 As shown in a, DPA / GB is composed of C, N, O and Ca elements. The full XPS spectrum shows that DPA has been successfully loaded into the DPA / GB gel beads, and there is a synergistic effect of coordination and hydrogen bonding interaction between them. 3+ In addition, DPA / GB scanning electron microscopy showed that the surface of DPA / GB gel beads was smooth ( Figure 3 b), the surface shows an entangled porous structure ( Figure 3 c). In addition, the cross-sectional SEM image shows that the gel beads have an interlaced honeycomb structure ( Figure 3 d). The pore structure of DPA / GB can accommodate adsorbates and is expected to have good adsorption performance. In addition, the XRD spectrum of DPA / GB shows broad amorphous diffraction peaks near 23.6° and 41.8° ( Figure 3 e), which is consistent with the diffraction peak of SA / GB. This indicates that the doping of DPA does not change the amorphous structure of DPA / GB. Finally, BET characterization shows that the specific surface area of ​​DPA / GB is 1.91 m 2 / g, the average pore size is 4.67 nm ( Figure 3 f).

[0013] 3. DPA / GB fluorescence performance analysis 1. DPA / GB vs. REE 3+ Selectivity The effect of DPA / GB on Tb was studied by fluorescence spectrometry 3+ / Eu 3+ The fluorescence emission spectrum was tested under the conditions of excitation wavelength of 280 nm and voltage of 500 V. In addition, the effect of DPA / GB on Tb 3+ / Eu 3+The fluorescence response of Tb 3+ / Eu 3+ Changes in the fluorescence intensity of characteristic emission peaks.

[0014] like Figure 4 As shown in Figure 2, DPA / GB only has weak emission in the range of 350 nm to 650 nm. 3+ After immersion in the solution, DPA / GB-Tb 3+ 、DPA / GB-Eu 3+ Obvious green and red light emissions appeared, and obvious characteristic emissions appeared in the fluorescence spectrum. The fluorescence intensity of 544 nm / 615 nm was enhanced by about 28 times and 8 times, respectively. 3+ The fluorescence emission intensity of the gel beads after being immersed in the solution remained almost unchanged, indicating that DPA / GB can selectively detect Tb 3+ 、Eu 3+ Two rare earth ions.

[0015] 2. pH for DPA / GB detection of Tb 3+ / Eu 3+ Impact Considering the changes in the surface charge properties, carboxyl groups and lanthanide ions caused by pH-induced protonation / deprotonation, we studied the effect of pH on the sensing performance. The results showed that the change in pH did not affect the fluorescence intensity of DPA / GB itself. However, when Tb 3+ or Eu 3+ (100 µ When the solution pH changes from 2 to 12, the green / red emission intensity at 544 / 615 nm increases rapidly first and then decreases, reaching a maximum value at pH 5.0 ( Figure 5 ). The possible reasons for this phenomenon are: when the pH value is lower than 5.0, the N and O atoms of DPA / GB are protonated; when the pH value is higher than 5.0, the carboxyl groups are deprotonated. In addition, under alkaline conditions, REE(OH)3 precipitation (K sp Value is about 10 -30 ), resulting in Ln 3+ Therefore, unless otherwise specified, the solutions in this patent are all kept at a pH of 5.0.

[0016] 3. DPA / GB vs. Tb 3+ / Eu 3+ Detection sensitivity and anti-interference performance test The sensing performance of DPA / GB is expressed by the limit of detection (LOD). 3+ / Eu 3+The detection limit was calculated according to the method reported in the literature [Chem. Sci., 2023, 14, 4901] (Formula 2).

[0017] Where LOD and σ represent the detection limit of DPA / GB and the standard deviation of DPA / GB blank samples, respectively, and S is the slope of the linear equation. The standard deviation σ of the blank sample is calculated by (Equation 3).

[0018] in X DPA / GB to Tb 3+ / Eu 3+ The fluorescence intensity of the ion, X i DPA / GB to Tb 3+ / Eu 3+ The average fluorescence intensity ratio of . N is the number of tests, N=15.

[0019] We pass Tb 3+ / Eu 3+ The change of concentration gradient further explored the effect of DPA / GB on Tb 3+ / Eu 3+ Sensing performance. Figure 6 (a, b) It can be seen that at 0.2-1000 / 6-600 µ M range, as Tb 3+ / Eu 3+ The increase in Tb concentration 3+ / Eu 3+ The characteristic emission peak intensity is enhanced. Figure 6 (c, d) show that the gel beads and Tb are calculated by the Benesi-Hildebrand equation. 3+ / Eu 3+ The binding constant K a They are 3.92×10 4 / 6.55×10 3 M -1 .like Figure 6 As shown in (e, f), the fluorescence intensity at 544 / 615 nm is related to Tb 3+ / Eu 3+ Concentration 0 / 5 µ M to 100 / 40 µ There is a good linear relationship within the concentration range of M (R 2 =0.99 / 0.98). The calculated DPA / GB to Tb 3+ / Eu 3+ The detection limit was as low as 0.23 / 0.85 nM.

[0020] In addition, in order to test the anti-interference ability of DPA / GB gel beads, other REE 3+ (Dy 3+ 、Tm 3+ 、Ce 3+ 、Lu 3+ 、Sm 3+ , Er 3+ , Pr 3+ 、Ho 3+ , Er 3+ 、Nd 3+ ,La 3+ ) and environmental metal ions (Na + , K + Mg 2+ , Ba 2+ , Ca 2+ , Fe 3+ 、Al 3+ ) exists ( Figure 7 ), found DPA / GB-Tb 3+ and DPA / GB-Eu 3+ There is no obvious change in fluorescence intensity and luminescent color, and fluorescence detection is almost not interfered by the above-mentioned rare earth ions of the same type and environmental ions.

[0021] 4. DPA / GB adsorption of Tb 3+ / Eu 3+ 1. Isothermal adsorption experiment and isothermal adsorption model Unless otherwise specified, all adsorption experiments were performed at pH = 5.02 and 25 ◦ C. All tested solutions were μ After filtration with M membrane, ICP-MS was used to determine Tb before and after adsorption. 3+ / Eu 3+ The isothermal / kinetic adsorption experiment steps are as follows: Adsorption isotherm experiment: DPA / GB gel beads (200 mg) were added to 3 mL of 2-40 / 2-40 mmol / L Tb 3+ / Eu 3+ The mixture was oscillated on a constant temperature oscillator for 2 h. After reaching adsorption equilibrium, the supernatant was taken out and the Tb before and after adsorption was detected using an ICP-MS instrument. 3+ / Eu 3+ Each experiment was conducted in triplicate. 3+ and Eu 3+ The DPA / GB after that is respectively DPA / GB-Tb 3+ and DPA / GB-Eu3+ express.

[0022] DPA / GB vs Tb 3+ / Eu 3+ The adsorption capacity of DPA / GB was calculated according to formula (4). 3 + / Eu 3+ The adsorption capacity of the experimental data was fitted and analyzed using the Langmuir (Formula 5), ​​Freundlich (Formula 6) and Temkin (Formula 7) isothermal models, and the fitting equations are as follows: In the formula C 0 and C e (mg / L) respectively represent Tb 3+ / Eu 3+ The concentrations at the initial and equilibrium stages. V (mL) and m (mg) represent the volume of adsorbate solution and the mass of dry DPA / GB gel beads, respectively. K l (L / mg) is the Langmuir isotherm adsorption constant. K f and n is the empirical constant of the Freundlich isotherm equation. R (8.314 J / (K·mg)), T (K) b (L / mg), A They are gas constant, temperature constant, adsorption energy constant and binding force constant respectively.

[0023] 2. Kinetic adsorption experiment and kinetic adsorption model Adsorption kinetics experiment: DPA / GB gel beads (200 mg) were added to 3 mL of 6 mmol / L Tb 3+ / Eu 3 + The solution was shaken in a constant temperature water bath oscillator, and the supernatant at different adsorption times was drawn with a disposable syringe, and the Tb in the supernatant was determined by ICP-MS. 3+ / Eu 3+ Concentration, three parallel experiments were performed for each group of experiments. The adsorption capacity was calculated according to (Equation 4).

[0024] The kinetic properties of the adsorbents were evaluated by pseudo-first-order, pseudo-second-order, and intraparticle diffusion kinetic models to understand the Tb 3+ / Eu3+ The adsorption mechanism on DPA / GB gel beads, the fitting equation is as follows: In the formula q e and q t (mol / g) represents the equilibrium state and adsorption time of DPA / GB, respectively. t The adsorption amount under (min). k 1 (min -1 ), k 2 [g·(mol·min) -1 ]and k i [g·(mol·min) -1 ] are the pseudo-first-order and pseudo-second-order adsorption rate constants and the diffusion rate constant within the i-th stage particles, respectively. C i for q t Adsorption time t The intercept of the fitted equation.

[0025] 3. Kinetic model analysis Adsorption rate is an important factor in evaluating adsorbents. The adsorption kinetic model not only reflects the adsorption mechanism of the adsorbent, but also reflects the factors that control the adsorption rate during the mass transfer of the adsorbate from the liquid phase to the solid phase. 3+ / Eu 3+ The adsorption kinetics of DPA / GB gel beads were investigated in aqueous solution. Figure 8 a / 8c is the gel beads adsorbing Tb 3+ / Eu 3+ Kinetic curve of Tb 3+ / Eu 3+ The adsorption data were fitted by pseudo-first-order kinetic model (Pfo), pseudo-second-order kinetic model (Pso) and intraparticle diffusion (Ipd) model. The fitting results are shown in Table 1. The results show that DPA / GB has a great influence on the adsorption of Tb 3+ / Eu 3+ The adsorption of α-β ... 2 =0.99 / 0.99) is significantly higher than pseudo-first-order kinetics (R 2 =0.98 / 0.96). This result shows that DPA / GB has an 3+ / Eu 3+The adsorption mechanism is mainly based on chemical adsorption.

[0026] Further evaluation of Tb by intraparticle diffusion model 3+ / Eu 3+ Adsorption behavior of gel beads on DPA / GB for Tb 3+ / Eu 3+ The adsorption process of MgO is controlled by three different adsorption stages. Figure 8 As shown in b / 8d, the fitting results show that DPA / GB is proportional to Tb 3+ / Eu 3 + The adsorption process is divided into three different stages. The first stage is the intraparticle diffusion stage. 3+ / Eu 3+ The concentration is high, and the surface of the gel ball has a large number of adsorption sites, Tb 3+ / Eu 3+ The adsorption activity sites on the surface of the gel spheres are quickly occupied by Tb in the second stage. 3+ / Eu 3+ In the stage of gradual adsorption, Tb 3 + / Eu 3+ Diffusion into the internal channels of DPA / GB. Due to the decrease in rare earth ion concentration and the adsorption of Tb 3+ / Eu 3+ The hindrance to its inward diffusion slows down the adsorption rate; the third stage is the adsorption equilibrium stage. 3+ / Eu 3+ The decrease of concentration and the reduction of adsorption sites will lead to the decrease of DPA / GB on Tb 3+ / Eu 3+ The adsorption amount no longer increases and reaches adsorption equilibrium. Figure 8 b, 8d, it can be seen that DPA / GB has an effect on Tb 3+ / Eu 3+ The intra-particle diffusion rate constant in the first stage is significantly higher than that in the other two stages, and none of the three stages on the curve passes through the origin of the coordinate, indicating that DPA / GB has a significant effect on Tb in the initial stage. 3+ / Eu 3+ The adsorption rate is the fastest, and the adsorption process is affected by the diffusion within the particles, but it is not the only factor controlling the adsorption rate.

[0027] 4. Isothermal adsorption model analysis The adsorption isotherm model reflects the 3+ / Eu 3+Changes in the adsorption of DPA / GB at different initial concentrations. 3+ / Eu 3+ The effect of DPA / GB on Tb 3+ / Eu 3+ The adsorption isotherm of Fig. 9 As shown in the figure, after fitting and analyzing the experimental data, the effect of DPA / GB on Tb 3+ / Eu 3+ The maximum adsorption capacity of Tb is 270 / 301 mg / g. In addition, the adsorption data were analyzed by Langmuir, Freundlich and Temkin model fitting, and the fitting parameters are shown in Table 2. The results show that the Langmuir model can better describe the adsorption of Tb than the Freundlich model. 3+ / Eu 3+ The adsorption behavior on DPA / GB belongs to monolayer adsorption. The Langmuir isotherm adsorption constant K l The size of K is used to judge the adsorption characteristics. l =0 is irreversible adsorption, 0<K l <1 is favorable for adsorption reaction, K l =1 for linear adsorption, K l >1 is an unfavorable adsorption reaction. The Langmuir constant K of this experiment l All satisfy 0<K l <1. In addition, the coefficient n in the Freundlich model is related to the difficulty of the adsorption process. When n<1, the adsorption process is difficult. When 1<n<2, the adsorption process is less restricted. When n>2, the adsorption process is favorable. DPA / GB adsorption of Tb 3+ / Eu 3+ The n values ​​of the fitted data are all between 1 and 2, indicating that DPA / GB has a significant effect on Tb 3+ / Eu 3+ Adsorption reaction occurs easily.

[0028] 5. DPA / GB Visualization Detection and Adsorption Mechanism 1. Test methods for quantum yield and fluorescence lifetime In the absolute quantum yield (QY) and fluorescence lifetime test of rare earth luminescent materials, DPA / GB, DPA / GB-Tb 3+ 、DPA / GB-Eu 3+ The excitation wavelength is 280 nm, and the emission peaks at 494 nm, 544 nm, and 615 nm are used as detection positions. The quantum yield is defined as the number of fluorescent photons emitted by the luminescent material (Lem ) and the number of photons of the excitation light absorbed (L abs ) ratio. The calculation formula is formula 11: When testing the fluorescence lifetime, the single photon counting method is first used to measure the corresponding relationship between fluorescence intensity and time and establish a fluorescence lifetime curve. Then, the three-exponential formula (Formula 12) is used for fitting, and the average lifetime is calculated according to (Formula 13): I : Any t Fluorescence intensity at the time; I 0 : Fluorescence intensity at the initial moment; A 1 、A 2 represents two different laser pulse amplitudes; τ is the fluorescence lifetime).

[0029] 2. DPA / GB visual detection mechanism Selective detection of Tb based on DPA / GB 3+ / Eu 3+ First, we discuss the effect of DPA / GB on Tb 3+ / Eu 3+ It is well known that REE 3+ Due to the f→f forbidden transition of the 4f electron layer, the luminescence itself is weak, while the organic ligand has good light absorption ability and sensitizes the REE through the "antenna effect". 3+ The triplet excited state (T1) energy of the ligand DPA is 25510 cm -1 , and Tb 3+ / Eu 3+ The excited state 5 D4(20500 cm -1 ) / 5 D0(17500 cm -1 ) energy matching, that is, DPA / GB can achieve Tb 3+ / Eu 3+ However, according to literature reports, the vibration of high-energy covalent bonds such as OH will cause REE 3+ Non-radiative decay of REE 3+ The characteristic luminescence of Tb will be quenched by the H2O molecules involved in the coordination. Since DPA / GB contains 94% water, we used transient fluorescence to evaluate the effect of water in DPA / GB on Tb 3+ / Eu 3+ The effect of luminescence. No Tb adsorbed 3+ / Eu3+ Before the experiment, the fluorescence lifetime (τ) and absolute quantum yield (Φ) of DPA / GB were 0.14 ms and 0.6%, respectively. Fig.10 ,11). After adsorption, DPA / GB-Tb 3+ / DPA / GB-Eu 3+ The lifetime and quantum yield were increased to 1.21 / 0.56 ms and 33.1% / 8.9% ( Fig.11 , 12). Explain DPA / GB-Tb 3+ and DPA / GB-Eu 3+ The number of coordinated water molecules in the material is 2.49 and 3.54 respectively. 3+ / Eu 3+ The abnormally strong luminescence phenomenon after the reaction is probably due to the absorption and stabilization of excess water by the gel matrix (SA), thereby suppressing the non-radiative decay caused by OH vibration coupling.

[0030] 3. DPA / GB adsorption mechanism The effects of DPA / GB on Tb were investigated by FTIR and XPS characterization. 3+ / Eu 3+ The adsorption mechanism of Fig.13 As shown in a, adsorption of Tb 3 + / Eu 3+ C=O (1600 cm -1 )、COOH (1410 cm -1 ) and COC (1020 cm -1 ) have weakened. In addition, the fitting peak at 399.70 eV of the N1s fine spectrum of DPA / GB before adsorption is attributed to the pyridine N on DPA. Fig.13 b. In the O1s spectrum, the four fitted peaks at 530.53 eV, 531.52 eV, 532.65 eV, and 533.54 eV are respectively attributed to C=O, -OH, CO, and OC=O groups ( Fig.13 In the C1s spectrum, the four fitting peaks at 284.83, 286.66, 288.26 and 288.85 eV are derived from CC / CH / C=C, CO / COC, C=N and C=O, respectively. However, in the case of adsorption of Tb 3+ / Eu 3+ After that, the N 1s fitting peak corresponding to DPA / GB shifted from 399.70 eV to 401.86 / 407.10 eV, indicating that Tb 3+ / Eu 3+ There is a strong coordination effect between it and pyridine N. Tb 3+ / Eu3+ In the 3d spectrum, the fitting peaks at 1276.81 / 1154.64 eV and 1242.37 / 1135.70 eV are respectively assigned to Tb 3+ / Eu 3+ of 3 d 3 / 2 and 3 d 5 / 2 absorb( Fig.13 e), indicating that DPA / GB successfully adsorbed Tb 3+ / Eu 3+ In addition, adsorption of Tb 3+ / Eu 3+ The fitting peaks on the O 1s spectrum move toward higher binding energy, and the center positions of the four fitting peaks move to 531.01 / 530.97 eV, 531.77 / 531.65 eV, 532.71 / 532.84 eV, and 533.74 / 533.83 eV, respectively. This is because the O atoms bind to Tb 3+ / Eu 3+ The coordination interaction between N and O atoms leads to the decrease of oxygen electron density. At the same time, new peaks of O-Tb and O-Eu appear at 530.13 eV and 530.23 eV. 3+ / Eu 3+ There is a strong coordination interaction between them, and the binding energies of the three fitting peaks of CO / COC, C=N and C=O on C 1s are weakened by 0.34 / 0.08 eV, 0.46 / 0.36 eV and 0.28 / 0.25 eV respectively. 3+ / Eu 3+ There is no coordination effect between O and N and the carbon atom, and the fitting peak position of CC / CH / C=C does not change. The above results show that DPA / GB mainly realizes the coordination of Tb through the coordination between O and N and rare earth ions. 3+ / Eu 3+ In addition, the TGA characterization results ( Fig.13 f) shows that DPA / GB adsorbs Tb 3+ / Eu 3+ After that, the material DPA / GB-Tb 3+ and DPA / GB-Eu 3+ The collapse temperatures of DPA / GB and Tb / GB were 18℃ and 11℃ higher than those of DPA / GB, respectively. 3+ / Eu 3+ There is a coordination effect [Nano. Lett., 2023, 23, 11916-11924].

[0031] In addition to the coordination effect mentioned above, there is also Ca 2+ and REE 3+ The ion exchange between the two was confirmed by the Ca 2p fine spectrum fitting results and EDS analysis. Fig.14 As shown in a, the Ca 2p spectrum before adsorption has two independent fitting peaks at 347.82 eV and 351.39 eV. 3+ / Eu 3+ After addition, the Ca 2p fitting peak area decreased significantly, and the peak position moved to 347.64 / 347.73 eV and 351.21 / 351.32 eV with lower binding energy, which was due to the reduction of Ca atomic content. EDS characterization results showed that DPA / GB contained C, N, O and Ca elements, which was consistent with the XPS results ( Fig.14 b), in which the Ca content is 46.76 wt%. Adsorption of Tb 3+ / Eu 3+ After the adsorption, the element contents of Tb / Eu increased from 0 to 1.07 / 0.48 wt%, and the element contents of Ca decreased to 26.89 wt% and 40.12 wt%, respectively. 2+ With Tb 3+ / Eu 3+ The exchange of ions between them.

[0032] Based on the above mechanism analysis, DPA / GB gel beads adsorb Tb 3+ / Eu 3+ The mechanism is (1) O and N atoms in DPA / GB and Tb 3+ / Eu 3+ Coordination and complexation between the two groups; (2) Ion exchange: Ca 2+ With Tb 3+ / Eu 3+ Ion exchange between.

[0033] 6.DPA / GB material cost calculation Material cost is one of the key issues in practical applications. An ideal adsorbent material should have both good adsorption performance and price advantages. DPA / GB material cost analysis shows (Table 3) that the total cost of 1g of dry DPA / GB is only $0.25, which is lower than traditional adsorbent materials.

[0034] In summary, the present invention uses calcium as a crosslinker to dope DPA and SA to prepare a sustainable composite material (DPA / GB) that integrates visual detection and efficient adsorption / recovery. DPA / GB has been successfully used in Tb3+ / Eu 3+ DPA as a sensitizer gives DPA / GB the ability to detect Tb in aqueous solution. 3+ / Eu 3+ Visual detection function; O and N atoms in the material give Tb 3+ / Eu 3+ The porous structure of the gel beads provides sufficient binding sites to encapsulate Tb 3+ / Eu 3+ At pH=5.02, DPA / GB has a strong adsorption capacity on Tb 3+ / Eu 3+ Detection limits as low as 0.23 / 0.85 nM (36.55 / 129.17 ppt); for Tb 3+ / Eu 3+ The adsorption capacity is 270 / 301 mg / g (1.72×10 −3 / 1.98×10 −3 mol / g). The preparation cost of the gel beads is only $0.25 / g. 3+ / Eu 3+ It provides important experimental basis for visual detection and preparation of efficient adsorption materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Appearance photos of DPA / GB in (a) water, (b) air, and (c) freeze-dried under fluorescent light, and (d) thermogravimetric curve of DPA / GB; Figure 2 (a) FTIR spectra of SA, DPA and DPA / GB, (b) Raman spectroscopy characterization of DPA / GB; Figure 3 (a) XPS spectrum of DPA / GB; (b, c) surface SEM images of DPA / GB; (d) cross-sectional SEM image of DPA / GB; (e) XRD spectrum of DPA / GB; (f) adsorption / desorption curve of DPA / GB; Figure 4 DPA / GB vs REE 3+ (a) Fluorescence response spectrum and (b) photograph under 254 nm UV light; Figure 5 DPA / GB in HEPES buffer solution with different pH values ​​(a) Tb 3+ / (b)Eu 3+ Fluorescence emission spectra before and after immersion in solution; Figure 6 0.2-1000 / 6-600 µM range, DPA / GB detection (a) Tb 3+ / (b)Eu 3+ Fluorescence emission spectra of (c)Tb; DPA / GB detection 3+ / (d)Eu 3+ Benesi-Hildebrand fitting equation; (e) Fluorescence intensity at 544 / (f) 615 nm varies with Tb 3+ / Eu 3+ Concentration change curve and LOD calculation; Figure 7 For REE 3+ , K + 、Na + , Ca 2+ Mg 2+ , Ba 2+ , Fe 3+ 、Al 3+ Fluorescence detection of DPA / GB (a, b) Tb 3+ 、(c,d)Eu 3+ The impact of Figure 8 (a) Tb adsorption on DPA / GB 3+ / (c)Eu 3+ Kinetic curves and (b) Tb 3+ / (d)Eu 3+ Intraparticle diffusion model fitting of adsorption data; Fig. 9 (a) Tb adsorption on DPA / GB 3+ / (b)Eu 3+ Isotherm adsorption curve of Fig.10 is the fluorescence lifetime of DPA / GB under 280 nm excitation; Fig.11 DPA / GB, DPA / GB-Tb 3+ and DPA / GB-Eu 3+ The quantum yield (λ ex =280 nm); Fig.12 (a) DPA / GB-Tb 3+ and (b) DPA / GB-Eu 3+ The fluorescence lifetime (λ ex =280 nm); Fig.13 Adsorption of Tb on DPA / GB 3+ / Eu 3+ (a) FTIR spectra before and after, (b) N 1s, (c) O 1s, (d) C 1s, (e) Tb3+ 3d / Eu 3+ Comparison of 3d fine spectrum and (f) thermogravimetric curve; Fig.14 Adsorption of Tb on DPA / GB 3+ / Eu 3+ Before and after (a) Ca 2p XPS spectra; (b) DPA / GB, (c) DPA / GB-Tb 3+ , (d) DPA / GB-Eu 3+ Changes in element content and EDS photos. DETAILED DESCRIPTION

[0036] The instruments and reagents used in the present invention are as follows: Scanning electron microscopy (SEM) was measured by Hitachi Regulus 8100 instrument; X-ray diffraction (XRD) was measured by RigakuSmart Lab 3KW equipment. Fourier transform infrared spectroscopy (FT-IR) was measured by Thermo Scientific NicoletiS50 FT-IR spectrometer. X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA), energy dispersive X-ray spectroscopy (EDX), specific surface area and pore size distribution were tested by ThermoScientific Escalab 250Xi, Netzsch STA449F3, Edax Elect Plus and Micromeritics ASAP 2020, respectively; steady-state fluorescence, quantum yield and fluorescence lifetime were tested using Edinburgh FLS1000 spectrometer; the instrument for preparing the buffer solution was a pH-3c pH meter, and the pH of the HEPES buffer was 5.02 (10 mM). The concentration changes of Tb³⁺ / Eu³⁺ were recorded by an inductively coupled plasma mass spectrometer (CAPQ, Thermo, Waltham, USA), and the fluorescence spectra were recorded by an FL970 fluorescence spectrometer (Techcomp, China).

[0037] The water used in the experiment was double distilled water, the analytical grade solvent dimethyl sulfoxide was purchased from Tianjin Damao Reagent Company, and REE(NO3)3·6H2O (REE 3+ = Eu 3+ , Tb 3+ 、Dy 3+ 、Tm 3+ 、Ce 3+ 、Lu 3+ 、Sm 3+ , Er 3+ , Pr 3+ 、Ho 3+ , Ga 3+ 、Nd 3+ ,La3+ , purity 99.99%), calcium chloride (CaCl2), sodium alginate (SA), and pyridine-2,6-dicarboxylic acid (DPA) were purchased from Beijing innochem. N-(2-hydroxyethyl)-piperazine-N'-(3-propanesulfonic acid) was purchased from Aladdin Reagent Company, Shanghai, China.

[0038] Example 1 Preparation of gel beads SA (200 mg) was dissolved in deionized water (5 mL) to obtain a 3.8 wt% SA solution; 5 mL of DPA (5.98 mM) solution was slowly added under stirring at 60 °C and stirred for 12 h to completely mix. The obtained DPA sol was added dropwise into 20 mL of 1 wt% calcium chloride solution using a syringe, and after crosslinking with calcium ions for 2 h, DPA / GB gel beads of uniform size were obtained. Finally, the surface Ca was removed by rinsing with deionized water. 2+ After removing impurities, store in deionized water until use.

[0039] Example 2 DPA / GB gel beads for Tb 3+ 、Eu 3+ Visual detection The DPA / GB gel beads were immersed in rare earth ions Tb 3+ 、Eu 3+ 、Tm 3+ 、Ce 3+ 、Dy 3+ 、Lu 3+ 、Sm 3+ , Pr 3+ 、Ho 3 + ,La 3+ 、Nd 3+ , Er 3+ , Yb 3+ In the solution, if the solution shows obvious green fluorescence and the fluorescence intensity is significantly enhanced, it means that Tb 3+ Solution; if obvious red fluorescence appears and the fluorescence intensity is significantly enhanced, it means that it is Eu 3+ Solution. DPA / GB to Tb 3+ 、Eu 3+ The detection limits were as low as 0.23nM and 0.85nM (36.55ppt, 129.17ppt), respectively.

[0040] Example 3 DPA / GB gel beads for Tb 3+ 、Eu 3+ Adsorption DPA / GB gel beads (200 mg) were added to 3 mL of 6 mmol / L Tb 3+ / Eu3+ In solution. At 25 ◦ C constant temperature water bath oscillator for adsorption, Tb 3+ 、Eu 3+ The adsorption capacities were 270 mg / g and 301 mg / g (1.72×10 − 3 mol / g、1.98×10 −3 mol / g).

Claims

1. A method for preparing sodium alginate supramolecular gel beads, characterized in that: Sodium alginate was dissolved in deionized water to obtain a sodium alginate solution, and pyridine-2,6-dicarboxylic acid solution was slowly added under stirring conditions at 55-65°C, and stirring was continued for 10-15 hours to completely mix the solution. The obtained sol was added dropwise into a calcium chloride solution, and DPA / GB gel beads were obtained after cross-linking reaction with calcium ions at room temperature for 1-3 hours.

2. The method for preparing the sodium alginate supramolecular gel beads according to claim 1, characterized in that: The mass ratio of sodium alginate to pyridine-2,6-dicarboxylic acid is 75:2~40:

1.

3. The method for preparing the sodium alginate supramolecular gel beads according to claim 1, characterized in that: The concentration of the calcium chloride solution is 1 wt %; the mass ratio of sodium alginate to calcium chloride is 2:1~3:

1.

4. Use of the sodium alginate supramolecular gel beads prepared by the method of claim 1 in the detection of terbium and europium ions.

5. The use of the sodium alginate supramolecular gel beads in the detection of terbium and europium ions according to claim 4, characterized in that: The DPA / GB gel beads were immersed in rare earth ions Tb 3+ 、Eu 3+ 、Tm 3+ 、Ce 3+ 、Dy 3+ 、Lu 3+ 、Sm 3+ , Pr 3+ 、Ho 3 + ,La 3+ 、Nd 3+ , Er 3+ , Yb 3+ In solution, DPA / GB-Tb 3+ The solution showed obvious green fluorescence, and the fluorescence intensity was significantly enhanced; DPA / GB-Eu 3+ The solution showed obvious red fluorescence and the fluorescence intensity was significantly enhanced, while the fluorescence of other rare earth ion solutions did not change significantly.

6. Use of the sodium alginate supramolecular gel beads prepared by the method of claim 1 in the adsorption of terbium and europium ions.